PENGARUH MEDIA LABYRIN CHART OF CHILDREN TERHADAP KECERDASAN INTERPERSONAL ANAK USIA 4-5 TAHUN DI TK ISLAM AKRAMUNNAS KOTA PEKANBARU - Egit Alpionita Sari; Zulkifli N N; Yeni Solfiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of study is to know the effect of media labyrin chart of children towards interpersonal intelligence of children aged 4-5 years in TK Islam Akramunnas Pekanbaru. The method of this research used experimental method with using pretest-postest control group design. The samples used in this study were 30 students. The data collection technique used is observation. Technique of data analysis used t-test by using program of SPSS 22. The research hypothesis was to find the effect of media labyrin chart of children towards interpersonal intelligence of children aged 4-5 years in TK Islam Akramunnas Pekanbaru. Based on data analysis was known that tcalculated = 4,184 > ttable = 2.048 with Sig. (2-tailed) = 0.000. Because Sig < 0.05 it can be concluded that there is difference of interpersonal intelligence that was be done before and after of media labyrinth chart of children. It can be interpreted that there is effect of media labyrin chart of children towards interpersonal intelligence of children aged 4-5 years in TK Islam Akramunnas Pekanbaru significant that is equal to 45.346%. Keyword: Interpersonal Intelligence, Media Labyrin Chart of Children